2022-RA-1276-ESGO Pembrolizumab monotherapy for advanced clear cell gynaecological cancer: phase II PEACOCC trial. (20th October 2022) - Miller, Rowan E; Clamp, Andrew; Gourley, Charlie; Roux, Rene; Hall, Marcia; Devlin, Michael-John; Nirsimloo, Rachel; Kounnis, Valentinos; Hughes, Laura; Counsell, Nicholas; Farrelly, Laura; Kristeleit, Rebecca S
Abstract : Introduction/Background: Advanced clear cell gynaecological cancers (CCGC) have poor prognosis with objective response rates (ORR) to second-line chemotherapy between 0–8%. Preliminary clinical activity with PD-1 inhibitors have been described in CCGC. We investigated pembrolizumab monotherapy for advanced CCGC. Methodology: PEACOCC is a Phase II, multicentre, single-arm trial in patients with advanced CCGC who had ≥1 prior line of chemotherapy with progression (PD) at study entry. Pembrolizumab 200 mg iv q21 days was given until PD (RECIST v1.1), unacceptable adverse event (AE), 2 years (y) pembrolizumab completed, patient or clinician decision. Primary endpoint was progression-free survival (PFS) rate at 12 weeks (w) (H0 ≤15%; H1 ≥33%; 5% 1-sided α; 90% power). Secondary endpoints included ORR, duration of response (DOR), PFS, overall survival (OS) and safety. Results: 49 patients were enrolled with 48 evaluable. Median age 58.5 y (32–77 y), ECOG 0/1 54.2%/45.8%, 85.4% ovarian CCGC. Median number of prior systemic therapy 2 (1–6); 19 patients (39.6%) had received anti-angiogenic therapy. 42 patients completed median of 4 cycles pembrolizumab (1–25), 6 patients (12.5%) continue pembrolizumab. 16.7% patients had Grade(G)3 treatment-related AE (TRAE) of hyperthyroidism, acute kidney injury, raised alanine aminotransferase, raised alkaline phosphatase, anaemia, encephalitis and diabetic ketoacidosis. There were no G4 or G5 TRAE. 3 patients (6.3%) discontinued pembrolizumab due to TRAEs. The PFS rate at 12w was 43.8% (90%CI:31.5–56.6) exceeding the pre-stated lower bound of 15%. Best ORR was 25.0% (90%CI:15.1–37.3) [1 complete, 11 partial], with 1 y DOR rate 47.7% (95%CI:14.1–75.6). After a median follow-up of 2.1 y, median PFS was 12.2w (95%CI:5.9–32.9) and median OS 71.0w (95%CI:29.1–137.6). Conclusion: The PEACOCC trial suggests that pembrolizumab is effective in heavily pre-treated patients with advanced CCGC: 43.8% patients were alive and progression-free at 12w. Clinical outcomes were durable with limited toxicity. These promising results justify consideration of pembrolizumab monotherapy as a new standard-of-care for advanced CCGC.